A ß-Secretase Modulator Decreases Tau Pathology and Preserves Short-Term Memory in a Mouse Model of Neurofibrillary Degeneration - Tautou, Marie; Eddarkaoui, Sabiha; Descamps, Florian; Larchanché, Paul-Emmanuel; El Bakali, Jamal; Goveas, Liesel Mary; Dumoulin, Mélanie; Lamarre, Chloé; Blum, David; Buée, Luc; Melnyk, Patricia; Sergeant, Nicolas (Frontiers in Pharmacology, 2021)
Identifying which among several in cellulo pharmacological activities is necessary for the proper in vivo activity is essential for further drug development against Alzheimer’s disease pathophysiological processes. An in-depth structure-activity relationship-based study has been carried out and two molecules named, MAGS02-14 and PEL24-199, that share a -secretase modulatory effect associated or not to a lysosomotropic activity in cellulo, have been identified. In terms of the chemical formulae MAGS02-14 and PEL24-199 only differ from each other by a single nitrogen atom. The study aims to elucidate the in vivo pharmacological effects of lysosomotropic and/or the beta-secretase modulatory activity in a Tau pathology mouse model. To address this question, the THY-Tau22 transgenic model of tauopathy was treated with both compounds for 6 weeks in a curative paradigm. Short-term memory, Tau burden, and inflammatory processes were analyzed using orthogonal methods and PEL24-199, but not MAGS02-14 was shown to restore the short-term memory and reduce the neurofibrillary degenerating process. These effects were associated with a reduced phosphorylation of Tau, an increased phosphatase expression, and decreased astrogliosis. Our results, therefore, suggest that the lysosomotropic activity may be non-essential for the effect on both Tau pathology.